Polyandry Practice in Muslim Communities: A Study on the Nagari Paninggahan Community, Junjung Sirih District, Solok Regency - Salma, Rahmi Febriyanti; Khairina, Khairina; Nabilah, Wardatun (Institut Agama Islam Negeri Batusangkar, 2024)
The main problem in this thesis is the factors that cause the perpetrator to commit polyandry, the reason for the guardian to marry a daughter who still has a husband and the impact of polyandri on community life in Nagari Paninggahan, Junjung Sirih District, Solok Regency. The results of this study were found: First, the factors that cause perpetrators to commit polyandri in Nagari Paninggahan, Junjung Sirih District, Solok Regency are divided into two forms, namely: internal factors in this case there are three factors, namely low understanding of religion and education, less harmonious households and age and external factors there are also three factors, namely the economy, long-distance relationships between husband and wife and social media. Second, there are three reasons for guardians to marry girls who still have husbands in Nagari Paninggahan, Junjung Sirih District, Solok Regency, namely: to improve the economy of children and grandchildren, girls get pregnant out of wedlock with other men who are not her husbands and the guardian is forced to marry a daughter. Third, the impact of polyandry on community life in Nagari Paninggahan, Junjung Sirih District, Solok Regency is threefold, namely: poor public views of polyandtry perpetrators and their families, defamation of housing and education and damage to children's future.